2021
DOI: 10.1177/16878140211062679
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and parameter identification of seated human body with the reference vector guided evolutionary algorithm

Abstract: The low frequency vibration of the vehicle in motion has a great influence on the ride comfort of occupants. The research on the vibration response characteristics of human body plays a great role in analyzing and improving ride comfort. The purpose of this study was to investigate the parameter identification of seated human body dynamic model. A seven-degree-of-freedom (DOF) lumped parameter model was established to describe the vibration response characteristics of human body. The derivation processes of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The transmission of vibration through a seat depends on the mechanical impedance of the body supported by the seat. Thus, SEAT and STHT have been used in the literature to predict or optimize ride comfort [1,10,[28][29][30]. In the following Equations ( 9) and ( 10), SEAT and STHT are defined, respectively.…”
Section: Eight-dof Lumped-parameter Model With Default Parameter Valuesmentioning
confidence: 99%
“…The transmission of vibration through a seat depends on the mechanical impedance of the body supported by the seat. Thus, SEAT and STHT have been used in the literature to predict or optimize ride comfort [1,10,[28][29][30]. In the following Equations ( 9) and ( 10), SEAT and STHT are defined, respectively.…”
Section: Eight-dof Lumped-parameter Model With Default Parameter Valuesmentioning
confidence: 99%
“…For instance, Bae and Kang, Shao et al, and Huang et al (2020) [10,15,16] optimized the parameters of 2-, 3-, 4-, and 5-DOF models using the gradient-based MATLAB function, called "fmincon". Zhang et al [17] introduced a reference vector-guided evolutionary algorithm to obtain the parameters of a 7-DOF human model, whereas Zhao et al [18] explored multi-objective and genetic algorithms (GAs) for parameter identification of a 5-DOF model. From these studies, it was found that the separate or hybrid application of these optimization techniques is usually associated with trade-offs that include an exhaustive search for initial values, randomly generated optimal solutions, high computation time, and generation of estimated parameters that do not reflect the dynamic response of the human body to WBV [6,19].…”
Section: Introductionmentioning
confidence: 99%